Influence De La Luminosite Nocturne Sur Le Comportement Migratoire De La Civelle D'Anguille (Anguilla Anguilla L.) Dans L'Estuaire De L' Adour ... - de Casamjor, M.-N.; Bru, N.; Prouzet, P. (ASC 1998 - N, 2024)
No abstracts are to be cited without prior reference to the author.Glass-eels migratory movements according to environnementals conditions were studied on Adour estuary during the 1997 catch season. These observations took place at night, during flood tide, ten kilometers upstream the sea transversal limit, on a sector of twelves kilometers in length where we observed the propagation of tide. Glass-eels densities (in g per 100m3) were estimated with fine mesh nets on five sampling stations. On each station, 3 longitudinal transects were sampled simultaneously in surface and close to the bottom. Catch abundance between November and Marsh, followed that tendency with a pick in January. These seems to indicate that abundance of glass-eels at the mouth of the river followed a Gaussian curve gives the basic abundance variation. Movement into the water column were induced by moonlight intensity. Glass-eels migrated mainly close to the bottom when turbidity is low and moonlight intensity is high. Moon phases and ...